PERSEPSI SISWA TERHADAP PEMBELAJARAN E-LEARNING DI SMA NEGERI 1 MERBAU KABUPATEN KEPULAUAN MERANTI - Nengsih, Sri Wahyu; Tugiman, Tugiman; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Social distancing becomes a heavy choice for every country especially in Indonesia in implementing policies for Covid-19 prevention. Because this policy has a negative impact on all aspects of life. The education sector is also affected by this policy. Government decisions that suddenly dismiss or move the learning process from school or madrasa to home, making various parties confused. The transition of this way of learning forces various parties to follow the path could be taken so that learning can continue and the choice is to use technology as a learning medium. SMA Negeri 1 Merbau is located on D.I Panjaitan street Teluk Belitung urban village Merbau Sub-district Kepulauan Meranti district. This study aims to explore the student’s perceptions of e-Learning. The research method used in this research is descriptive method in which the type of research is exploratory research. Where, exploratory research is research conducted for problems that have not been studied more clearly. Using descriptive (exporure) method. The research results obtained froms students perceptions of e-Learning are that they like e-Learning. The percentage of the result of the data shows that thera are 8 students or (12,7%) who answered very likes, who answered 41 students like or (65,1%), answered 9 students don’t like (14,3%) and answered very dislike there are as many as 5 students or (7,9%). Then the percentage of adoption statements about no difficulties faced by 10 students or (15,9%) stated stroungly agree, 38 students or (60,3%) stated agree, 11 students or (17,5%) stated disagree and as many as 4 student or (6,3%) stated that they strongly disagree.Key Words: Students' Perceptions Of E-Learning In Sma Negeri 1 Merbau Meranti Island